Determinants of Sustainable Development Goals (SDGs) in Indonesia: Mapping with Cartesius Diagram - Azwardi, Azwardi; Sukanto, Sukanto; Rohima, Siti (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2024)
This research aims to explore the long- and short-term relationships and the quality of interactions between variables within the framework of the Sustainable Development Concept, focusing on the social aspect (Human Development Index), economic aspect (economic growth), and environmental aspect (Environmental Quality Index) in the context of reducing poverty rates in Indonesia. The methodology employed is the Panel Vector Error Correction Model (P-VECM) analysis for panel data, combining time series (2010-2022) and cross-section data (34 provinces in Indonesia), along with a Cartesian diagram to identify which provinces have the greatest potential for achieving evenly distributed SDG progress. The results show that the Granger causality test reveals no one-way or two-way causal relationships or interactions between the human development index, economic growth, and environmental quality index. In the long-term analysis, only the human development index significantly impacts poverty, with a negative correlation. In contrast, economic growth and the environmental quality index do not have a long-term relationship with Indonesia's poverty levels. These findings suggest that improving the quality of education, healthcare, and living standards in the long term can effectively reduce poverty, especially in Indonesia. Pro-poor government policies are crucial to prevent widening inequality and ensure that economic growth benefits the upper class and the lower and middle classes through more equitable income distribution.